PENEGAKAN HUKUM TERHADAP KENDARAAN DENGAN SUARA KNALPOT YANG MELEBIHI BATAS KEBISINGAN DI KOTA GORONTALO - MA’RUF, YONAL (Ganec Swara, 2025)
Law enforcement against vehicles with exhaust noise exceeding the noise limit in Gorontalo City is an important effort in maintaining environmental quality and public health. Noise produced by motor vehicles can cause health problems and pollute the tranquility of the city. The implementation of regulations regarding vehicle exhaust noise limits in Gorontalo City is an important issue related to environmental quality management and public health. Noise produced by motor vehicle exhausts can disturb the tranquility, damage the health of residents, and pollute the urban environment. This study aims to evaluate the implementation of regulations on vehicle exhaust noise limits, with a focus on the effectiveness of supervision, law enforcement, and challenges faced in field practice. The results of the study indicate that although there are regulations governing noise limits, their implementation is still limited by various factors, such as the lack of adequate noise measurement facilities and the low level of public awareness regarding the importance of compliance with these regulations. More serious efforts are needed in terms of law enforcement, public education, and improving measurement facilities to create a more comfortable and healthy environment in Gorontalo City.